The ability of organization commitment and moderate worked motivation by the effect of budget goal clarity in budgetary inaccuracy - Sari, I Gusti Ayu Dewi Indira; Dwirandra, A.A.N.B. (International research journal of management, IT and social sciences, 2019)
In term of designing activity and budgeting for organization, the goal of this research is to explore and understand the effects of budget goal clarity on the inaccuracy of budgeting that moderate by organizational commitment and worker motivation. Population of research is all department under the postgraduate program of Udayana University. Samples are choosing by total sampling method and data that collected should meet with pre-request of assumption test. Data were analyzed by Binary Logistic Regression Analysis. The result of this research showed that: (1) budget goal clarity is negative significant effect the budgeting unaccuracy; (2) organizational commitment are increased the negative effect of budgeting goals on budget unaccuracy; (3) worked motivation increased the negative effect of the clarity of budgeting on budgeting unaccuracy.